(untitled) (American Journal of Islam and Society, 1998)
The natural counterpart of a free market economy is a politics of insecurity. If ’capitalism’ means ’the free market,’ then no view is more deluded than the belief that the future lies with ’democratic capitalism’ .... the free market cannot last in an age in which economic security for the majority of people is being reduced by the world economy ... a reform of the world economy is needed that accepts a diversity of cultures, regimes and market economies as a permanent reality.